2010
DOI: 10.1002/adfm.201000329
|View full text |Cite
|
Sign up to set email alerts
|

Control of Optical Hysteresis in Block Copolymer Photonic Gels: A Step Towards Wet Photonic Memory Films

Abstract: Polystyrene‐block‐poly(2‐vinyl pyridine) (PS‐b‐P2VP) block copolymer photonic gels are fabricated that exhibit controllable optical hysteresis in response to a cyclic pH sweep. The optical hysteresis is tuned by controlling the ion‐pairing affinity between various anions and the protonated pyridinium ions on the P2VP block, which is highly dependent on the hydration energy of the ions, the dielectric constant of the solvent, and the ionic strength of the medium. The pH coercivity defining the magnitude of hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 50 publications
1
79
0
Order By: Relevance
“…[34][35][36] The X-ray photoelectron spectroscopy measurement of the functionalized textile indicated that the grafting of the block copolymer on the surface of the textile was achieved via a very small number of 2-vinylpyridine monomer units, and most of the pyridyl groups on P2VP-b-PDMS copolymer remained unchanged during the grafting process, which preserved the pH-responsive property of P2VP (Supplementary Figure S1). CA measurements were first conducted in air to probe the responsive wettability of the functionalized textile surface by using water droplets with different pH (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36] The X-ray photoelectron spectroscopy measurement of the functionalized textile indicated that the grafting of the block copolymer on the surface of the textile was achieved via a very small number of 2-vinylpyridine monomer units, and most of the pyridyl groups on P2VP-b-PDMS copolymer remained unchanged during the grafting process, which preserved the pH-responsive property of P2VP (Supplementary Figure S1). CA measurements were first conducted in air to probe the responsive wettability of the functionalized textile surface by using water droplets with different pH (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…43,44 All the AFM measurements were carried out in the same location near the edge of a scratch. The average thickness of the hybrid layer was found to be 30.4 nm at pH 5.5 and 63.4 nm at pH 2.5.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have demonstrated that block copolymer lamellar structures are useful for creating tunable photonic crystals. [26][27][28][29][30] For instance, the lamellae assembled from polystyrene-b -quaternized poly(2-vinyl pyridine) (PS-b -QP2VP) exhibited strong refl ective colors when the QP2VP layers were selectively swollen with solvents. In this case, photonic stop bands (PSBs) varied with the extent of swelling, and which can be controlled by crosslinking density and the species of counter-anions pairing with pyridinium groups.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%
“…[26][27][28][29] Briefl y, in-plane oriented lamellar fi lms were fi rst prepared by spin casting PS 57 -b -P2VP 57 solution (Number-average molecular weight (M n ) of each block is 57 × 10 3 g/mol and 57 × 10 3 g/mol for PS and P2VP respectively, PDI = 1.08, 6 wt% in propylene glycol monomethyl ether acetate) onto glass followed by annealing the fi lms in chloroform vapor at 50 ° C for 2 days. The thickness of the fi lms was controlled to ∼ 1 μ m. The P2VP blocks were then quaternized using iodomethane in hexane at 50 ° C for 24 hours.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%